Hubungan Pembinaan Keluarga Kristen dan Etika Hidup Kudus terhadap Keharmonisan Rumah Tangga Kristen - Donalia Reynaldo; Nurlela Oematan (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2025)
This research aims to analyze the relationship between Christian Family Discipleship and Ethics of Holy Living toward achieving Christian Household Harmony. The Christian family is understood as a covenant institution whose primary purpose is sanctification and discipleship. Harmony within the household is viewed not merely as the absence of conflict, but as genuine peace (shalom) founded upon biblical principles. The methodology utilized in this study is a descriptive qualitative approach based on literature review, assuming that data is derived from surveys/literature studies involving Christian families. The independent variables tested are the consistency of Christian Family Discipleship practices (as the means/process) and the application of the Ethics of Holy Living (as the standard/morality), while the dependent variable is the level of Household Harmony. The research findings indicate a positive and significant relationship between Christian Family Discipleship and the Ethics of Holy Living, both simultaneously and partially, regarding Christian Household Harmony. Family Discipleship serves as a tool that actively trains and internalizes spiritual values, while the Ethics of Holy Living, especially the principles of forgiveness, Agape love, and humility, function as the normative foundation that must be lived out. It was found that the synergy between a consistent Discipleship process and the practice of Holy Ethics produces a stable and transformative harmony, supported by the unity of spiritual purpose and covenant-based conflict resolution mechanisms. This study concludes that strengthening Christian Household Harmony requires investment in Discipleship that gives rise to the Ethics of Holy Living, which should be the main focus of church ministry and parental responsibility.